(untitled) (Agroindustrial Science, 2024)
Noodles are currently highly consumed products, which are commonly made with wheat flour, since it is one of the most produced grains worldwide; however, the gluten content in its composition can affect the health of consumers. It is a great challenge for the industry to produce foods low in gluten. The aim of this research was to evaluate the partial substitution of wheat flour by modified white carrot starch (A. xanthorrhiza) in the preparation of noodles. A completely randomized design with factorial arrangement A*B+1 was used to evaluate the chemical characteristics of starch (native and chemically modified) and the physicochemical, rheological and sensory characteristics of the noodles. It was observed that total starch and amylopectin content decreased significantly when starch was chemically modified, while amylose increased considerably. On the other hand, using 100% wheat flour presented higher moisture (10.14%); ash (0.70%); protein (14.44%) and gluten (14.44%); while, when using 100% modified starch of the two ecotypes, low levels of gluten were obtained (0.001). In relation to the rheological characteristics, 25% and 50% modified starch of both ecotypes allowed obtaining similar results to the control treatment. Finally, it was demonstrated that the addition of 75% modified starch of ecotype ECU 18989 gave the best intensities of odor (4.95), flavor (4.95), aftertaste (6.05) and firmness (6.65).